In Silico and In Vivo Approaches to Exploring the Antidiabetic of Vegetable Fern (Diplazium esculentum S.) - Iljannah, Nissa; Sapitri, Nazwa Martina; Rizki, Alfath Muhammad; Yuningsih, Lela Mukmilah; Khumaisah, Lela Lailatul; Kurniawan, Isman (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by increased blood glucose levels (hyperglycemia). Efforts to treat and prevent DM are made by using antidiabetics, usually synthetic drugs. However, continuous use may cause side effects. Other alternatives are needed to handle DM by utilizing plants as antidiabetics, such as the vegetable fern (Diplazium esculentum S.). Therefore, this research aims to analyze the components of a vegetable fern leaf extract and determine its effectiveness as an antidiabetic through in silico and in vivo assays. The sample was macerated using 98% ethanol for 3x24 hours. Phytochemical screening and LC-MS/MS analysis were performed on the extract. In vivo studies were conducted on mice with extract doses of 200, 400, and 600 mg/BW along with positive (Glibenclamide) and negative controls. An in silico study was conducted by molecular docking against the ɑ-glucosidase receptor with PDB ID 5KZW, which was docked to 18 compounds from the extract. The analysis revealed that the D. esculentum S. leaf extract contained 22 compounds, including flavonoids, terpenoids, steroids, and phenolics. The best dosage for the in vivo antidiabetic efficacy assays was 400 mg/BW of extract, which significantly reduced glucose levels for 21 days, reaching 30%, which was better than Glibenclamide's 27%. Based on in silico tests, the molecules kaempferol 3-rhamno-glucoside and 4,4-Bis[2,2-bis(4-methoxyphenyl)vinyl]biphenyl had the highest affinity, with a value of -6.3 kcal/mol. Dantaxusin A and Phorone A came in second and third, respectively, with -6.0 and -5.9 kcal/mol. These results suggest the potential antidiabetic effects of D. esculentum S. leaf extract.